Quantitative analysis of targeted lipidomics in the hippocampus of APP/PS1 mice employing the UHPLC-MS/MS method - Shiyu Xiao; Xuemeng Wei; Bing Han; Xiaoqian Shi; Congzhen Wei; Rumeng Liang; Jingna Sun; Zheng Zhang; Zhengang Han; Li Shen (Frontiers in Aging Neuroscience, 2025)
BackgroundAlzheimer’s disease (AD) is marked by the pathological features of amyloid-β plaque accumulation, as well as intracellular neurofibrillary tangles formation in the patients’ brain. Aberrant lipid metabolism is increasingly recognized as one of the important contributors to AD.PurposeThe main goal of this research was to conduct quantitative detection of targeted lipidomics in hippocampal tissue of APPSwe/PS1dE9 mice in order to identify lipid metabolic biomarkers of early-onset AD mice.MethodsOur approach departs from conventional lipid detection methods, employing a highly accurate quantificational Ultra High Performance Liquid Chromatography Tandem Mass Spectrometry (UHPLC-MS/MS) technique to analyze targeted lipid biomarkers. The innovative method was utilized to detect targeted lipids in the hippocampus of AD and wild-type mice. Statistical method was performed by Student’s t-test and multivariate analysis. Differential metabolites were identified through fulfilling the standard of Variable Importance in Projection surpassing one and the significance probability lower than 0.05 thresholds.ResultsBoth groups utilized identical methodologies and adhered strictly to standardized treatment protocols. Sphingolipids (SPs), Glycerophospholipids (GPs), Glycolipids, Glycerides (GLs), Sterol Lipids (STs), and Free Fatty Acid (FA) were identified as prominent lipids exhibiting alterations in the hippocampus of AD models. Regarding glycolipid and glycerolipid composition, monogalactosyldiacylglycerols (MGDGs) and Triacylglycerols (TGs) constituted a significant proportion (p < 0.05, VIP > 1). Among glycerophospholipids, phosphatidylethanolamines (PEs) and phosphatidylcholines (PCs) emerged as significant constituents (p < 0.05, VIP > 1). Furthermore, hexosylceramides (HexCers) and ceramides (Cers) in the AD model’s hippocampus, the prominent sphingolipids in the hippocampus of AD mice, existed as the two primary changed lipid metabolites. The levels of some TGs in GLs and CEs in STs showed a significant elevation (p < 0.05, VIP > 1). In contrast, most kinds of MGDGs, HexCers, Cers, PEs and FA (18:2) demonstrated a notable decrease in the hippocampus of AD group (p < 0.05, VIP > 1).ConclusionThe present research represents the important quantitative identification of distinct lipid biomarker profiles within the hippocampal portion of 7.5-month-aged AD mice. It encompasses glycolipid, GLs, GPs, SPs, STs, and FAs using a targeted HPLC-MS method for quantification. These findings suggest potential diagnostic lipid biomarkers in hippocampus of early-onset AD mice related to cellular membrane integrity, atherosclerosis, oxidative stress damage, and inflammation.